2016
DOI: 10.1080/14767058.2016.1177815
|View full text |Cite
|
Sign up to set email alerts
|

Variable effect of maternal oral glucose load on circulating cell-free placental mRNAs

Abstract: Maternal fasting state does not influence expression of the majority of placenta-specific genes but may need to be accounted for when validating biomarkers of placental disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Low vitamin B12 levels during pregnancy alter adipose-derived circulating miRNAs, which may mediate an adipogenic and insulin-resistant phenotype, leading to obesity [248]. Maternal fasting seems not to affect circulating placenta-specific transcripts [249]. Gardiner et al [250] found 55 miRNAs in serum significantly altered through alcohol use during pregnancy.…”
Section: Free Rnas and Pathologiesmentioning
confidence: 99%
“…Low vitamin B12 levels during pregnancy alter adipose-derived circulating miRNAs, which may mediate an adipogenic and insulin-resistant phenotype, leading to obesity [248]. Maternal fasting seems not to affect circulating placenta-specific transcripts [249]. Gardiner et al [250] found 55 miRNAs in serum significantly altered through alcohol use during pregnancy.…”
Section: Free Rnas and Pathologiesmentioning
confidence: 99%